S98 Early Clinical Experience with Pirfenidone For Idiopathic Pulmonary Fibrosis (IPF) in the UK: Interim Results from a UK Cohort. (19th November 2012) - Parfrey, H; Leonard, C; Gibbons, MA; Harris, E; Frank, R; Sharp, C; Dew, RM; Maher, TM
Abstract : Introduction and Objectives: In March 2011, the novel anti-fibrotic, pirfenidone (Esbriet®), became the first drug to be licenced in Europe for the treatment of IPF. Since September 2011 pirfenidone has been available in the UK through a named patient programme (NPP). We present initial findings from a real-world study describing clinical experience with pirfenidone in routine UK clinical practise. Methods: A multi-centre, retrospective, cohort review was undertaken across 4 NHS Trusts. Data (through to July 2012) were collected from the clinical records of individuals receiving pirfenidone for IPF through the NPP. Results: Data was available from 68 patients (72% Male). Mean (±S.D.) age at diagnosis was 67.3±8.1 years. At initiation of pirfenidone FVC was 69.4±21.5% predicted and DLco 39.8±15.3% predicted. Domiciliary oxygen was being administered to 38.2% (26/68). At day 15, following a 14-day titration period, 92.3% (60/65) were receiving the recommended dose of 2403 mg/day pirfenidone. One patient had discontinued treatment. Data was available for 53 patients at 3 months; 42 (79.2%) continued to receive pirfenidone, whilst 11 (20.8%) had stopped therapy. Between 3 and 6 months, 93.1% (27/29) continued pirfenidone with only 2 further patients (6.9%) stopping treatment. Of the 68 patients, 30 (44.1%) experienced an adverse drug reaction (ADR) resulting in a change of dose or cessation of pirfenidone. The commonest ADRs were GI-upset and photosensitive rash. Of those experiencing ADRs, with data available, 12/22 (54.5%) continued pirfenidone after a dose-reduction. In 53 patients for whom pre-treatment liver function tests were available, only two showed a minor increase above the upper limit of normal. During the observation period 10.3% (7/68) of patients suffered an acute exacerbation. Collection of data to determine effect of pirfenidone on lung function at 6 months of treatment is on-going. Conclusions: Patients enrolled in the NPP are demographically representative of the UK IPF population but have moderately severe disease that is on average more advanced than that seen in the CAPACITY study. Pirfenidone treatment is reasonably well tolerated. On-going observation of patients enrolled in the UK NPP should provide invaluable insights into the real-world benefits of pirfenidone in individuals with IPF.